If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(4x + 6) + -1ln(3) = 12 Reorder the terms: nL(6 + 4x) + -1ln(3) = 12 (6 * nL + 4x * nL) + -1ln(3) = 12 (6nL + 4nxL) + -1ln(3) = 12 Reorder the terms for easier multiplication: 6nL + 4nxL + -1 * 3ln = 12 Multiply -1 * 3 6nL + 4nxL + -3ln = 12 Reorder the terms: -3ln + 6nL + 4nxL = 12 Solving -3ln + 6nL + 4nxL = 12 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-6nL' to each side of the equation. -3ln + 6nL + -6nL + 4nxL = 12 + -6nL Combine like terms: 6nL + -6nL = 0 -3ln + 0 + 4nxL = 12 + -6nL -3ln + 4nxL = 12 + -6nL Add '-4nxL' to each side of the equation. -3ln + 4nxL + -4nxL = 12 + -6nL + -4nxL Combine like terms: 4nxL + -4nxL = 0 -3ln + 0 = 12 + -6nL + -4nxL -3ln = 12 + -6nL + -4nxL Divide each side by '-3n'. l = -4n-1 + 2L + 1.333333333xL Simplifying l = -4n-1 + 2L + 1.333333333xL Reorder the terms: l = 2L + -4n-1 + 1.333333333xL
| 2x+2-2x=6 | | cos(x)=0.95 | | (P-5)(p+3)=0 | | 80/65-8/13x | | -5(-3n+4)+3=2(1-2n) | | [(-42)(-6)]/(3-7) | | 4p-6=10 | | 8=a/3 | | 2x(3x-6)+5x=6x^2+9 | | 5x=6+51 | | 2/5:4/3 | | 4(2x-5)-6=-2x+8 | | 5x+5z=8+4y | | 5(2a-5)= | | 7/6x1/6 | | 8x+7z=7+5y | | 5x+9y=45whatsy | | 3/2x2/3x=13 | | 14x^2+45x-81=0 | | 11X+3=9x+5 | | -2a+3(3a+3)=4(-3a-3)+2 | | -8x=1/2 | | -5y+3=8y-4 | | 1×2=w/6 | | 18t-9/2=-12/8 | | (3x-5)(x^2-6x+4)=0 | | 1-12x=7(1+2x) | | x^2-714x+42194=0 | | 15/9=-1/3t-7/2 | | 2a=64 | | 6b^3-5b^2= | | 4x+(5x+2)=47 |